ACCURACY ASSESSMENT OF UTP GPS CONTINUOUSLY OPERATING REFERENCE STATION FOR SIMULATED STRUCTURAL DEFORMATION MONITORING - Mohd Yusof, Mohd Kamal (Universiti Teknologi PETRONAS, 2017)
Accuracy is a degree of closeness a set of data from series of measurement to its true value and data set could be said as precise if the value is close to the average value of the quantity that being measured. Data measurement for any engineering applications cannot be perfect but the accurate data is important especially when it comes to the human safety. Recently Universiti Teknologi PETRONAS (UTP) has established a continuously operating reference system (CORS) which can be used by Global Positioning System (GPS) users to enhance the accuracy of their application. However, being new the accuracy performance has been assessed. Therefore, this study took the initiative to assess the accuracy of the CORS, in two variables which are baseline between CORS and users as well as amount of data used to provide the positioning.